An investigation of the mechanical behavior of three-dimensional low expansion lattice structures fabricated via laser printing. (15th December 2018) - Mercer, C.; Lee, J.; Balint, D.S.
Abstract: A feasibility study of the fabrication of a specific type of low expansion lattice structure via 3-D laser printing has been conducted. In addition, a detailed baseline understanding of the mechanical response of a specific low thermal expansion lattice geometry has been established. The printed Ti-6Al-4V structures exhibit robust mechanical behaviour and fail via initial buckling followed by strengthening and then fracturing of the struts. Finite element simulation can predict the mechanical behaviour of the printed structures with a good degree of accuracy until the onset of buckling, which is the first point of failure. An analytical model has also been constructed, and homogenization techniques have been implemented to determine the effective stiffness and strength of the lattice structure arranged periodically to be used in sandwich panels. The analytical studies of the lattice structure performance show that the low CTE lattices are suitable for lightweight applications. Additionally, analysis has been performed to optimise the design of a bi-material lattice structure and the optimised design was found to have better performance compared to the bulk material while maintaining a low coefficient of thermal expansion for most cases studied. The techniques used in this paper can serve as a foundation for future studies to optimise and improve such lattice structures.